Fractional Euclidean Distance Matrices Extrapolator for Scattered Data - Pozniak, Natalija; Sakalauskas, Leonidas (Jaunųjų mokslininkų darbai, 2017)
The paper deals with application of fractional distance matrices to construct the efficient extrapolator of scattered data. The properties of fractional distance matrices are studied in order to develop the linear extrapolator. Study and comparison of developed extrapolator with Shepard extrapolator is performed by computer simulation.